TRAF3 Positively Regulates Host Innate Immune Resistance to Influenza A Virus Infection - Chen, Fangzhao; Chen, Liurong; Li, Yinyan; Sang, Huiting; Zhang, Chunyu; Yuan, Shuofeng; Yang, Jie (Frontiers in Cellular and Infection Microbiology, 2022)
Tumor necrosis factor receptor-associated factor 3 (TRAF3) is one of the intracellular adaptor proteins for the innate immune response, which is involved in signaling regulation in various cellular processes, including the immune responses defending against invading pathogens. However, the defense mechanism of TRAF3 against influenza virus infection remains elusive. In this study, we found that TRAF3 could positively regulate innate antiviral response. Overexpression of TRAF3 significantly enhanced virus-induced IRF3 activation, IFN-β production, and antiviral response, while TRAF3 knockdown promoted influenza A virus replication. Moreover, we clarified that inhibiting ubiquitinated degradation of TRAF3 was associated with anti-influenza effect, thereby facilitating antiviral immunity upon influenza A virus infection. We further demonstrated the key domains of TRAF3 involved in anti-influenza effect. Taken together, these results suggested that TRAF3 performs a vital role in host defense against influenza A virus infection by the type-I IFN signaling pathway. Our findings provide insights into the development of drugs to prevent TRAF3 degradation, which could be a novel therapeutic approach for treatment of influenza A virus infection.